JUST KEEP SWIMMING?: queer pooling and hydropoetics. Issue 1 (2nd January 2023) - Chow, Jeremy; Urcaregui, Maite
Abstract: By bringing queer ecologies to bear on the blue humanities, this essay promotes a queer hydropoetic investigation that attends to the forms, aesthetics, and politics of pools. Pools are sites of aquatic enjoyment, sport, and revelation that have long been understudied within the blue humanities. We ask whether the promises and failures of swimming in these geographies can provide a queer heuristic in which submersion, immersion, and staying afloat subtend coming out, queer eroticism, and queer of color coalitional politics. Our tripartite examination engages the independent film Saved! (2004), the ecosexual documentary Water Makes Us Wet (2019), and the young adult novel and graphic novel adaptation of Gabby Rivera's Juliet Takes a Breath (2016/2019 and 2020, respectively). Our analysis of pools, as intimate bodies of water that capture media and literature alike, reorients the blue humanities to consider closer proximities and smaller scales of water's queer potentiality.